2016
DOI: 10.1080/15384101.2016.1207835
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cells are capable of proliferation into adulthood in the transition region between the seminiferous tubules and therete testisin Wistar rats

Abstract: Sertoli cells (SCs) play a crucial role in testis differentiation, development and function, determining the magnitude of sperm production in sexually mature animals. For over 40 years, it has been considered that these key testis somatic cells stop dividing during early pre-pubertal phase, between around 10 to 20 days after birth respectively in mice and rats, being after that under physiological conditions a stable and terminally differentiated population. However, evidences from the literature are challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 64 publications
0
26
0
1
Order By: Relevance
“…Therefore, injecting the MSC secretome can help attract lost Sertoli cells from the pools of progenitor cells. This assumption was indirectly supported by the restoration of the Sertoli cell pool without visible proliferation at the observed control points in vivo , as well as the stimulation of Sertoli cell migration by MSC secretion in vitro (Figueiredo et al, 2016 ; Sagaradze et al, 2019a ).…”
Section: Mechanisms Of Msc Participation In Tissue Regenerationmentioning
confidence: 85%
“…Therefore, injecting the MSC secretome can help attract lost Sertoli cells from the pools of progenitor cells. This assumption was indirectly supported by the restoration of the Sertoli cell pool without visible proliferation at the observed control points in vivo , as well as the stimulation of Sertoli cell migration by MSC secretion in vitro (Figueiredo et al, 2016 ; Sagaradze et al, 2019a ).…”
Section: Mechanisms Of Msc Participation In Tissue Regenerationmentioning
confidence: 85%
“…Our results indicate that Sertoli cells are the main early target and the reservoir of persistent MARV in crab-eating macaque testes. These infected Sertoli cells may be replenished by some progenitor cells as the virus is cleared (Figueiredo et al, 2016). Interestingly, Sertoli cells were reported as a target of Zika virus in immunodeficient laboratory mice (Govero et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the Sertoli cells within the SV region have been shown not only to stably support GFRα1-positive undifferentiated spermatogonia through their constitutive GDNF expression, but also to be capable of proliferating even after puberty in rodents (Aiyama et al, 2015;Figueiredo, Franca, Hess, & Costa, 2016;Kulibin & Malolina, 2016). Such features are similar to those of somatic cyst progenitor cells in the SSC niche of Drosophila testes, in which somatic cyst progenitor cells are proliferative and contribute distally to cyst cells, the post-mitotic supporting cells that ensheath each gonialblast (de Cuevas & Matunis, 2011).…”
Section: Discussionmentioning
confidence: 99%